Dietary Components and Metabolites Are Associated with Liver Fibrosis in People Living with HIV (PLWH) in the MASH cohort. (29th May 2020) - Martin, Haley; Martinez, Sabrina Sales; Stebliankin, Vitalii; Tamargo, Javier; Campa, Adriana; Narasimhan, Giri; Baum, Marianna
Abstract: Objectives: Distinct dietary components and microbiome metabolites may affect liver disease progression, a common comorbidity among people living with HIV (PLWH). Similarly, diet composition, including micronutrients, have been associated with markers of HIV disease progression (CD4 cell count). The objective of this study was to investigate the associations between dietary components, plasma metabolites, and liver fibrosis in PLWH. Methods: A cross-sectional pilot study that enrolled 50 PLWH on antiretroviral therapy from the Miami Adult Studies on HIV (MASH) cohort. Diet quality was measured with the USDA Healthy Eating Index (HEI) and liver fibrosis was measured via the Fibrosis-4 Index (FIB-4). Microbiome metabolites were measured from plasma samples via metabolomics-non-targeted gas chromatography/mass spectrometry and liquid chromatography/mass spectrometry. Statistical analysis included T-test, Chi-square, Spearman correlation, and Partial Least Squares Discriminant Analysis (PLS-DA). Results: The participants' mean age was 55 ± 6.81, 58% were male, and 68% were African Americans. FIB-4 and HEI seafood/plant protein score were inversely correlated (rho = -0.320, P  = 0.022). There were also trends towards significance between CD4 cell count and seafood/plant protein score (rho = 0.251; P  = 0.078), and CD4 cell count and greens/beans HEI score (rho = 0.269; P  = 0.059). Microbiome metabolites that differed between the high and the low FIB-4 group using PLS-DA included 3-methylhistidine and phosphatidylcholine (PC) metabolites, often associated with meat consumption. Conclusions: Lower liver fibrosis and higher CD4 cell count, a measure of HIV disease progression, were associated with consumption of foods typically high in micronutrients and fiber (seafood, plant protein, greens, and beans) in PLWH. Additionally, higher levels of 3-methylhistidine and PC metabolites, biomarkers associated with higher meat intake, were associated with higher liver fibrosis scores. These relationships confirm similar findings in the literature. Higher meat and lower vegetable intake are known risk factors for liver disease. These findings may provide the basis for larger studies and potential targets for dietary intervention in this population. Funding Sources: National Institute on Drug Abuse and National Institute on Minority Health and Health Disparities.